KARAKTERISTIK PASIEN TUMOR OTAK DI RSUP H.ADAM MALIK MEDAN TAHUN 2021 - Amila, Amila; Sembiring, Evarina; Meliala, Sinarsi (Prodi Kedokteran Fakultas Kedokteran Universitas Malahayati, 2023)
Abstract: THE CHARACTERISTICS OF BRAIN TUMOR PATIENTS AT H.ADAM MALIK GENERAL HOSPITAL MEDAN IN 2021 Brain tumor is one of the 10 biggest causes of death, causing high morbidity and mortality that affects quality of life. The purpose of this study was to identify the characteristics of brain tumor patients at H. Adam Malik General Hospital Medan for the period January-December 2021. The design in this study used a cross-sectional approach. The population of this study were all brain tumor patients who visited H. Adam Malik General Hospital Medan as many as 30 people and this was a total sampling. The data obtained were analyzed using the percentage. The results showed that the majority were in the age category 46-65 years (56.7%), male (53.3%), high school/vocational school education (46.7%), self-employed (36.7%), stage I (50%), the majority have been sick for 1-3 years (43.3%) and the majority have socioeconomic status of IDR 1,600,000-2,500,000 for 12 people (40.0%). Suggested further research on the characteristics of brain tumors (location, size, number of tumors) that can affect the quality of life of brain tumor patients.Keywords : Tumor , Brain, Characteristics